Vaccination of piglets at 2 and 3 weeks of age with Ingelvac PRRSFLEX® EU provides protection against heterologous field challenge in the face of homologous maternally derived antibodies. Issue 1 (December 2016) - Balka, Gyula; Dreckmann, Karla; Papp, György; Kraft, Christian
Abstract Background Due to difficulties in eradicating porcine reproductive and respiratory syndrome (PRRS) linked to biosecurity challenges, transmission of the virus and the lack of efficient DIVA vaccines, successful control of PRRS requires a combination of strict management measures and vaccination of both sows and piglets. The present study aimed to assess the efficacy of a recently developed MLV vaccine (Ingelvac PRRSFLEX® EU) in piglets at 2 and 3-weeks of age in the presence of homologous maternally derived antibodies as the dams were vaccinated with the same vaccine strain (ReproCyc® PRRS EU). Methods The study was carried out on a Hungarian farrow to finish farm naturally infected with PRRSv. The study was designed as a blind, placebo controlled side by side trial. ORF5 sequence similarity of the vaccine strain and the resident field strain was 87.8 %. PRRS specific real-time quantitative PCR was performed from serum samples to measure both the viral load and the frequency of virus positive animals. Results At the time of the natural infection observed in the control group at 10–12 weeks of age, the number of viraemic animals did not increase significantly in the vaccinated group. To understand the infection dynamics, positive PCR samples with low Ct values were sequenced (ORF5) and the data analysis indicated the circulation of wild type virus in both groups, however wild type virus was only found in non-vaccinated animals. Conclusions Our data indicate that piglets vaccinated at as early as 2 weeks of age with Ingelvac PRRSFLEX® EU were protected both in terms of proportion of viraemic animals and viraemia levels. It has to be highlighted that these results were achieved in piglets with high levels of homologous maternally derived antibodies (MDA) at the time of vaccination.